Viral respiratory infections and air pollutants (2021)
Air pollution is a public health issue of global importance and a risk factor for developing cardiorespiratory diseases. These contaminants induce reactive oxygen species (ROS) and increased pro-infammatory cytokines such as IL-1β, IL-6, and IL-8,triggering the infammatory response that alters cell and tissue homeostasis and facilitates the development of diseases. The efects of air pollutants such as ozone, particulate matter (PM10, PM2.5, and PM0.1), and indoor air pollutants on respiratory health have been widely reported. For instance, epidemiological and experimental studies have shown associations between hospital admissions for individual diseases and increased air pollutant levels. This review describes the association and relationships between exposure to air pollutants and respiratory viral infections, especially those caused by the respiratory syncytial virus and infuenza virus. The evidence suggests that exposure to air contaminants induces infammatory states, modulates the immune system, and increases molecules’ expression that favors respiratory viruses’ pathogenesis and afects the respiratory system. However, the mechanisms underlying these interactions have not yet been fully elucidated, so it is necessary to develop new studies to obtain information that will allow health and policy decisions to be made for the adequate control of respiratory infections, especially in the most vulnerable population, during periods of maximum air pollution.